Analisis Hubungan Opini Pelaksanaan Perlindungan Covid-19 dengan Persepsi Pasien Tentang Kualitas Pelayanan di Ruang Rawat Jalan RSUD Kota Bogor Tahun 2021 - Mayline Angela Hutahayan (Yayasan Pendidikan Medika Indonesia, 2022)
In the Covid-19 pandemic, which is a health concern not just in Indonesia but around the world, the cases confirmed on March 10, 2021 included 117,332,262 confirmed cases and 2,605,356 deaths worldwide. In Indonesia, the number of case is increasing from month to month, which is certainly a major problem for the medical system. The number of hospitals that act as referral centers certainly requires that hospitals concern to the quality of services to their patients. One of the hospitals where patient visits have been reduced due to the effects of Covid-19 was Bogor City Hospital. The aim of this study is to analyze the connection between the implementation of COVID-19 protection and the perception of patient quality in the outpatient department of the Bogor City Hospital in 2021. Hospital was used as a sub-variable. This survey is a quantitative survey that uses a cross-sectional survey method and is aimed at 436 participants. The results of data analysis carried out on two Covid-19 protection sub-variables, respectively, there is a strong relationship between the sub-variable of the use of masks and the quality of service and there is a strong relationship between the sub-variables of cleanliness and sterilization of hospitals with quality of service.Keywords: Covid-19 Protection, Service Quality, Covid-19 Pandemic